2018
DOI: 10.3390/ijms19010319
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of the Balsaminaceae Sister Genera Hydrocera triflora and Impatiens pinfanensis

Abstract: The family Balsaminaceae, which consists of the economically important genus Impatiens and the monotypic genus Hydrocera, lacks a reported or published complete chloroplast genome sequence. Therefore, chloroplast genome sequences of the two sister genera are significant to give insight into the phylogenetic position and understanding the evolution of the Balsaminaceae family among the Ericales. In this study, complete chloroplast (cp) genomes of Impatiens pinfanensis and Hydrocera triflora were characterized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
8
14
1
Order By: Relevance
“…The results showed that the bias was significant in usage of synonymous codons except tryptophan and methionine in T. paniculatum as well as A/T ending rich in cp genome. These results revealed that the RSCU and codon usage exsited biased codon usage, which was consistent with previous reports in cp genomes of higher plants [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…The results showed that the bias was significant in usage of synonymous codons except tryptophan and methionine in T. paniculatum as well as A/T ending rich in cp genome. These results revealed that the RSCU and codon usage exsited biased codon usage, which was consistent with previous reports in cp genomes of higher plants [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…Of 22,964 codons, leucine (Leu) being the most abundant amino acid had a frequency of 10.56%, then isoleucine (Ile) with 8.54%, while cysteine (Cys) was rare with a proportion of 1.12% ( Tables S1 and S2 , Figure 4 ). Our study species genome is like other previously reported genomes which showed that leucine and isoleucine are more common [ 41 , 42 , 43 , 44 , 45 ]. Furthermore, comparable to other angiosperm chloroplast genomes, our results followed the trend of codon preference towards A/T ending which was observed in plastomes of two Aristolochia species [ 46 ], Scutellaria baicalensis [ 47 ], Decaisnea insignis [ 34 ], Papaver rhoeas and Papaver orientale [ 48 ] Cinnamomum camphora [ 49 ], and Forsythia suspensa [ 41 ].…”
Section: Resultssupporting
confidence: 81%
“…Among them, the numbers of penta-SSRs and mono-SSRs were 123 and 87, respectively, and accounted for 77% of the entire SSRs ( Figure 5A). These results are in sharp contrast to previous results regarding other taxa, in which mono-SSRs were the most abundant and penta-SSRs were rarely present [19,41,[43][44][45][46][47]. The largest number of SSRs was located in the LSC (232), followed by the SSC (37) and the IR (3) ( Figure 4B).…”
Section: Distribution Of Large and Simple Sequence Repeatscontrasting
confidence: 97%